KONSEP KELUARGA MAṢLAḤAH DALAM PERSPEKTIF QIRA’AH MUBADALAH DAN RELEVANSINYA DENGAN KETAHANAN KELUARGA DI MASA PANDEMI COVID-19 - Ramdan Wagianto (Institut Agama Islam Negeri Batusangkar, 2021)
This article discusses the concept of the maṣlaḥah family in the perspective of mubadalah and its relevance to family resilience during the Covid-19 pandemic. The maṣlaḥah family is a family whose members provide each other with primary needs that include physical and mental needs, and each others give rights and obligations. This paper is a literature research, with the descriptive-qualitative as method research and qira’ah mubadalah as the approach. The results showed that the concept of maṣlaḥah family in the perspective of qira’ah mubadalah is that in principle it prioritizes the concept of mufa’alah (kesalingan), meaning that there are no superior and no inferior parties in the family. In this case the maṣlaḥah family indicators that can be displayed are at least several principles, namely the zawaj principle (prinsip saling berpasangan), the mu’adalah Principle (prinsip keadilan), the muwazanah principle (prinsip keseimbangan), the mu’awanah principle (prinsip saling menolong), the Principle of musyawarah, the Principle of taradhin min huma (prinsip kerelaaan), and the Principle of mu’asyarah bil ma’ruf (prinsip saling berkomunikasi/bergaul dengan baik). The author can conclude that the concept of the maṣlaḥah family in the framework of mubadalah is that it has quite significant relevance if it is applied by every family, especially in the current Covid-19 pandemic.